MAPPING THE SPATIOTEMPORAL DYNAMICS OF SURFACE WATER AREA OF THE DABERAM WETLAND RESERVOIR USING DIGITAL EARTH AFRICA SANDBOX - Ako, Abbas Abdullahi; Nafisat, Bello; Usman, Lawal Sani (FUDMA Journal of Sciences, 2025)
A wetland reservoir is an area of land covered by water from rivers, lakes, aquifers, or springs. This research aimed at mapping the spatiotemporal dynamics of surface water extent of the Daberam wetland reservoir using Digital Earth Africa Sandbox, over 12 years. Multitemporal Landsat datasets and Water Observation from Space products were used. The data analysis and result presentation were carried out in the Jupyter Lab Environment of the Digital Earth Africa Sandbox. The result shows that the highest upward trend corresponds to only three 3 years of the study period, while the downward trend was observed in nine 9 years. The year 2015 is the period that the reservoir experienced maximum surface water extent, while 2019 is the year of the highest decline in the surface water extent. The maximum possible area extent of the surface water is 2.69 km2, but it declined to 0.71 km2. This shows a significant loss of 1.98 km2. The study established that the Daberam wetland reservoir has severely dried up due to the impacts of climate change and anthropogenic activities. Therefore, the study recommended that water extraction from the Daberam Wetland Reservoir for irrigation and other activities should be regulated, and encroachment on the floodplains of the reservoir should be discouraged. Lastly, the Katsina State Government should declare a state of emergency on the Daberam wetland reservoirs and initiate a rehabilitation project.
Keywords: Daberam; wetlands; water resource management; Katsina State